From lambs to lions : future security relationships in a world of biological and nuclear weapons - Preston, Thomas, 1963- (Rowman & Littlefield, 2007)
While many books discuss how nations can prevent the proliferation of biological and nuclear weapons, this unique and controversial volume begins with the premise that these weapons will certainly multiply despite our desperate desire to slow this process. How worried should we be and what should we do? In From Lambs to Lions, Thomas Preston examines current trends in the proliferation of nuclear and biological weapons capabilities, know-how, and technologies for both state and non-state actors-and then projects these trends over the coming ten to fifteen years to assess how they might impact existing security relationships between states. With a new preface to the paperback edition, Thomas Preston also addresses the threat of biological and nuclear weapons proliferation that faces the Obama administration. How might a nuclear North Korea or Iran constrain U.S. freedom of action in its foreign or military policies? How might U.S. security be impacted by the current biotechnical revolution and spread of bioweapons know-how to opponents? How might terror groups like Al Qaeda make use of such weapons in future attacks against the United States or its allies around the world? These are the central, most fundamental questions facing American security policy over the coming decades, and to ignore them is to put ourselves at risk for new 9/11-style surprises. For answers, and for some potentially surprising reassurances, this clear and informative book will be invaluable.